2014
DOI: 10.1007/s10439-014-1024-6
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Lymphatic Perfusion System for Independently Controlling Pressure Gradient and Transmural Pressure in Isolated Vessels

Abstract: In addition to external forces, collecting lymphatic vessels intrinsically contract to transport lymph from the extremities to the venous circulation. As a result, the lymphatic endothelium is routinely exposed to a wide range of dynamic mechanical forces, primarily fluid shear stress and circumferential stress, which have both been shown to affect lymphatic pumping activity. Although various ex-vivo perfusion systems exist to study this innate pumping activity in response to mechanical stimuli, none are capab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…In these simulations, axial pressure gradients affect pumping indirectly, by changing the level of NO. In agreement with experimental studies showing that imposed flow tends to inhibit contractions (68, 78, 95, 96), the simulations predict decreasing amplitude with increasingly negative (helping) axial pressures (Figure 4 b ). In addition, experimental observations have shown that the system is able to pump without endothelium-derived NO (87).…”
Section: Lymphatic Transport and Pumpingsupporting
confidence: 89%
“…In these simulations, axial pressure gradients affect pumping indirectly, by changing the level of NO. In agreement with experimental studies showing that imposed flow tends to inhibit contractions (68, 78, 95, 96), the simulations predict decreasing amplitude with increasingly negative (helping) axial pressures (Figure 4 b ). In addition, experimental observations have shown that the system is able to pump without endothelium-derived NO (87).…”
Section: Lymphatic Transport and Pumpingsupporting
confidence: 89%
“…In experimental studies conducted by controlling flow through cannulated ex vivo lymphatic preparations, contractions are affected by axial pressure gradients that either drive flow through the vessel (negative gradient) or force the vessel to pump against pressure (positive gradient) (52,(55)(56)(57)(58)(59)(60). In these experiments, imposed flow tends to inhibit contractions, and our simulations reproduce this behavior, predicting decreasing amplitude with increasingly negative (helping) axial pressures (Fig.…”
Section: Resultssupporting
confidence: 67%
“…To test the hypothesis of shear driven adaptation, experimental frameworks may be employed in which isolated vessels are subjected to alterations in the mechanical environment for an extended period of time. Devices have been proposed that can precisely and independently control the axial pressure gradient and the transmural pressure of an isolated vessel and measure contractile amplitude and frequency over time (Kornuta and Brandon Dixon 2014) and others have developed approaches for culturing functional lymphatic vessels for days (Gashev, Davis et al 2009). Application of such approaches to experimental frameworks on the order of days may be easily utilized to quantify adaptation of the contractile apparatus of lymphatic vessels in response to sustained changes in the mechanical environment.…”
Section: Discussionmentioning
confidence: 99%
“…These homeostatic values are on the order of 10 6 dyne/cm 2 for circumferential and axial stress and 10 1 dyne/cm 2 for shear stress; however, the stresses experienced by lymphatic vessels are notably lower than those in arteries and veins (Dixon, Greiner et al 2006, Zhang, Gashev et al 2007, Baeyens, Nicoli et al 2015). Recent reports suggest that lymphatic endothelial cells align maximally in response to shear stress values between 4 and 6 dyne/cm 2 (Baeyens, Nicoli et al 2015) and that the shear threshold in rat thoracic ducts that produces a change in contractility depends on the transmural pressure and is in the range of 0.5 – 1 dyne/cm 2 (Kornuta, Nepiyushchikh et al 2015). Homeostatic circumferential stress in these simulations was 40.5 kdyne/cm 2 , and homeostatic shear stress was 0.30 dyne/cm 2 .…”
Section: Discussionmentioning
confidence: 99%